The Wiley-Blackwell companion to cultural geography - Johnson, Nuala Christina, 1962-; Schein, Richard; Winders, Jamie (Chichester, West Sussex : Wiley-Blackwell, 2013)
"A significantly revised new edition of this authoritative reference volume which traces the historical evolution of cultural geography through to the very latest research"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Human geography; Electronic books